A Proposed Multi-Layer Firewall to Improve the Security of Software Defined Networks - AbdulRidha Hussein, Mohammed (International Journal of Interactive Mobile Technologies (iJIM), 2023)
one of the most important motivations behind the use of software-defined networking (SDN) is the desire to move from the approach of traditional networks to a more flexible and intelligent software development technology. This paper focuses on the importance of the SDN-based platform POX controller security firewall modules and its effectiveness on networks including the central administration of the SDN-based platform controller for protecting the network from possible attacks. The work is performed using the Mininet emulator with the aid of iperf bandwidth measurement tool. Result reveals that the proposed multi-layer firewall does not compromise the flexibility of the network in any way.